Activity, time, and subjective happiness: An analysis based on an hourly web survey - Hideaki Sakawa; Fumio Ohtake; Yoshiro Tsutsui (Osaka University, Institute of Social and Economic Research (ISER), 2015)
This paper investigates how people's happiness depends on their current activities and on time. We conducted an hourly web survey, in which 70 students reported their happiness every hour on one day every month from December 2006 to February 2008. This method is an extension of the experience sampling method (ESM), since it uses mobile phones and personal computers. Our new method has the same strength of ESM in that it can measure real-time happiness data and thus avoid reflection and memory bias. Using our new method, we can obtain diurnal happiness data of respondents and also grasp their behavior at each of their reporting times over 14 months. Analyzing the data of our survey, we found (a) happiness significantly depends on activities, hours, and months, (b) while most of the time-variation of happiness is attributable to the time pattern of activities, happiness varies predictably with the hour in a day, even when activities are controlled for, and (c) while activities affect both genders similarly, there are gender gaps in the diurnal happiness pattern after controlling for activities.
Keywords: I31; 330; happiness; hourly web survey; ESM; mobile phone; Japan